A Review on Cultural Customs of Marriage Traditions Among Banjar Ethnic Women in Banjarmasin Indonesia - Anwar Hafidzi; Masyitah Umar; Mohd Hatta Mohd Hani; Rusdiyah Rusdiyah (Institut Agama Islam Negeri (IAIN) Manado, 2021)
This study reveals the tradition of the Banjar inland tribes in their marriage rituals. For a Banjar ethnic woman, who adheres to her cultural customs, a marriage for them will only take place when it is arranged by the family. Arranged marriage means a marriage determined by the family with the prospective husband chosen by the family on certain factors. Family is the dominant factor that determines the future of a Banjar ethnic woman especially in the aspect of marriage. The research methodology used in this research is a literature review that reveals the secrets behind conventional marriage practices using a phenomenological approach. Firstly, this study found that for the Banjar ethnic group, traditionally arranged marriages are compulsory. Second, there is a culture of giving money in a nominal amount to the bride’s family before the wedding takes place. Third, the bride’s home must be filled with donations such as furniture or daily household necessities. If things as stated cannot be met, then the bride’s family will look for another prospective husband for her daughter. Such a marriage tradition is the practice and belief of the ancestors of the Banjar tribe, it is an ancient practice of dynamic animism.Keywords: Rituals; marriages; customs; Banjar; Indonesia.